Kearifan Budaya Lokal sebagai Benteng Munculnya Konflik Agama - Sidik, Muhammad Alfan (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
Practically religion and culture can’t be separated, although in the theoretical sphere they can be separated. Religion can be practiced by its adherents through culture. Basically Religion comes to humans who had been had a culture. Long before the coming of religion, in fact people with their intellect and conscience are able to have a noble culture, which saves each other and is able to create a harmonious life. However, it is precisely in this modern era when humans who claim to reach the peak of advanced culture, it is often a conflict in the name of religion. The birth of religion should be to complete the noble culture, in the contrary, religion and local culture indeed experience tension which trigger conflict sometimes. Humans who only had cultured, can life together in harmony although pre-religions. Unfortunately when there comes aren’t time in which religion and culture have been developed of there life aren’t harmonious. This paper will discuss the relationship between religion and culture in relation to conflict. Analysis of the crisis of modernity which also result in narrow-mindedness cause the emergence of conflic.